Evaluation of perceived social stigma and burnout, among health-care workers working in covid-19 designated hospital of India: A cross-sectional study - Bhumika Rajendrakumar Patel; Bhumi G Khanpara; Prakash I Mehta; Kishan D Patel; Nidhi P Marvania (Wolters Kluwer Medknow Publications, 2021)
Introduction: The coronavirus disease 2019 (COVID-19) pandemic has notably changed the working and community environment for health-care workers (HCWs) leading to burnout and feeling of being stigmatized by the community due to their work. This study aims at assessing the prevalence of burnout, perceived social stigma, and their demographic and work-related predictors. Methods: A cross-sectional study using Oldenburg Burnout Inventory and perceived stigma scale was carried out among 348 HCWs in COVID-19 designated hospital at Ahmedabad about 6 months after the onset of the outbreak in September 2020. The prevalence of burnout was assessed in two dimensions: disengagement and exhaustion. Severity of each was measured on low, moderate, and high levels. Results: Total 348 HCWs participated in study with a mean age of 28.05 ± 6.75 years. Two hundred and sixty-five (76.15%) HCWs experienced burnout and 200 (57.47%) high levels of perceived stigma. The level of burnout was measured on three severities. Factors which predict high burnout are female gender, lower education, unmarried status, living in a nuclear family, and high perceived stigma. Work characteristics such as duty hours, days of working, monthly income, and work experience does not predict burnout. Intern doctors had high burnout (87.25%, χ2 = 28.067, P < 0.001) while nurses had high perceived stigma (70.97%, χ2 = 14.307, P < 0.05). Perceived stigma is positively correlated with burnout (r = 0.26, P < 0.001) with its both components, disengagement (r = 0.19, P < 0.001) and exhaustion (r = 0.30, P < 0.001). Conclusion: Burnout and stigmatization are prevalent among HCWs. Psychological interventions needed to reduce their burden and improve quality care during pandemic.